Effects of Tissucol and epsilon aminocaproic acid in the healing process following dental extraction in dehydrated rats Efeitos do Tissucol® e do ácido épsilon aminocapróico no processo de reparo alveolar em ratos desidratados - Tetuo Okamoto; Maria Cristina Rosifini Alves-Rezende; Carolina Chiantelli Cláudio; Thaís da Silveira Rodrigues; Roberta Okamoto (Sociedade Brasileira de Pesquisa Odontológica, 2006)
A histological study was conducted of the alveolar bone healing process following tooth extraction of dehydrated rats after the implantation of fibrin adhesive (TISSUCOL) associated to previous irrigation of the wound with a 5% epsilon aminocaproic acid solution (EACA). Seventy two rats were used, divided into three groups receiving different treatments after the surgical procedure. In group I, the gingival mucosa was sutured after extraction of the right upper incisor. In groups II and III, chronic dehydration was produced by water deprivation for 9 days (3 days in the preoperative period and 6 days in the postoperative period). In the animals of Group II, after tooth extraction, the gingival mucosa was sutured in the same way as performed in group I. In group III, after extraction, the dental socket was irrigated with 5% EACA, followed by implantation of the fibrin adhesive (TISSUCOL). The mucosa was sutured in the same way as performed in the other groups. At 3, 7, 15 and 21 postoperative days, the animals were sacrificed in number of 6 for each group. Specimens containing the dental socket were removed and fixed in 10% formalin and decalcified in an equal part formic acid and sodium citrate solution. After routine processing, the specimens were embedded in paraffin for microtomy. We obtained 6 µm semi-serial slices that were stained with hematoxylin and eosin for histological evaluation. The results showed that the water deprivation in the pre- and postoperative periods caused a delay in the alveolar bone healing process. The use of the fibrin adhesive (TISSUCOL) produced an improvement in the fibrinolytic picture caused by dehydration. Foi estudada histologicamente a reparação do alvéolo dental de ratos desidratados, após o implante de adesivo fibrínico (TISSUCOL®) associado à irrigação prévia da ferida com solução a 5% de ácido épsilon-aminocapróico. Foram empregados 72 ratos, divididos em três grupos, que receberam diferentes tratamentos após o procedimento cirúrgico. No Grupo I, após a extração do incisivo superior direito, a mucosa gengival foi suturada. Nos Grupos II e III foi provocada a desidratação crônica pela privação de ingestão de líquidos durante 09 dias (3 dias no pré-operatório e 6 dias no pós-operatório), sendo que, no Grupo II, após a extração dental, a mucosa gengival foi suturada de forma semelhante à do Grupo I; no Grupo III, logo após a exodontia, o alvéolo foi irrigado com a solução de ácido épsilon-aminocapróico a 5%, seguida de implante de adesivo fibrínico (TISSUCOL®) e foi feita sutura da mucosa de forma semelhante à dos demais grupos. Decorridos 3, 7, 15 e 21 dias após o ato operatório, os animais foram sacrificados em número de 6 para cada grupo. A seguir, as peças contendo o alvéolo dental foram removidas e fixadas em formalina a 10% e descalcificadas em solução de ácido fórmico e citrato de sódio em partes iguais. Após processamento laboratorial de rotina, foram incluídas em parafina para microtomia. Foram obtidos cortes semi-seriados com 6 micrômetros de espessura, seguidos de coloração em hematoxilina e eosina para estudo microscópico. Os resultados obtidos mostram que a hidroprivação no pré e pós-operatório ocasiona profundo retardo no processo de reparo em feridas de extração dental. O emprego de adesivo fibrínico (TISSUCOL®) melhora o quadro fibrinolítico provocado pela desidratação.